ZhiJingSan Inhibits Osteoclastogenesis via Regulating RANKL/NF-κB Signaling Pathway and Ameliorates Bone Erosion in Collagen-Induced Mouse Arthritis - Ling, Yuanyuan; Yang, Jie; Hua, Di; Wang, Dawei; Zhao, Chenglei; Weng, Ling; Yue, Dandan; Cai, Xueting; Meng, Qinghai; Chen, Jiao; Sun, Xiaoyan; Kong, Weikang; et al. (Frontiers in Pharmacology, 2021)
Bone erosion is the most evident pathological condition of rheumatoid arthritis (RA), which is the main cause of joint deformities and disability in RA patients. At present, the conventional RA drugs have not achieved satisfactory effect in improving bone erosion. ZhiJingSan (ZJS), which is a traditional Chinese prescription composed of scolopendra (dried body of Scolopendra subspinipes mutilans L. Koch, scolopendridae) and scorpion (dried body of Buthus martensii Karsch, Buthus), exhibits anti-rheumatism, analgesic and joint deformities improvement effects. This study aimed to assess the therapeutic effect of ZJS on RA bone erosion and to elucidate the underlying mechanism. The effect of ZJS on RA bone erosion was investigated in a murine model of bovine collagen-induced arthritis (CIA), and the underlying mechanism was investigated in vitro in an osteoclast differentiation cell model. Administration of ZJS delayed the onset of arthritis, alleviated joint inflammation, and attenuated bone erosion in the CIA mice. Meanwhile, ZJS decreased the serum levels of TNF-α, IL-6, and anti-bovine collagen II-specific antibodies. Furthermore, ZJS treatment reduced the number of osteoclasts and the expression of cathepsin K in the ankle joints of CIA mice. ZJS also inhibited receptor activator of NF-κB ligand (RANKL)-induced osteoclast differentiation and the expression of MMP9 and cathepsin K in vitro. Mechanistically, ZJS blocked RANKL-induced p65 phosphorylation, nucleation, and inhibited the expression of downstream NFATc1 and c-Fos in bone marrow-derived macrophages (BMMs). Taken together, ZJS exerts a therapeutic effect on bone erosion in CIA mice by inhibiting RANKL/NF-κB-mediated osteoclast differentiation, which suggested that ZJS is a promising prescription for treating RA bone erosion.